The Role of Firm Size in Moderating the Relationship Between Environmental Accounting and Financial Performance of Listed Manufacturing Firms in Nigeria - Chris Awe-Mathias; Abiola Mikail Tonade; Sunday Olugboyega Kajola; Amos Adejare Aderibigbe (Sinergi International Journal of Accounting and Taxation, 2026)
This study determine the moderating role of firm size (FS) on the effect of environmental accounting (EA) on the financial performance (FP) of listed manufacturing firms in Nigeria. Secondary sourced from annual reports of 20 selected firms (2010–2024) were employed for the study. EA was proxied by environmental compliance cost (ECC), environmental protection cost (EPC), waste management expenditure (WME), energy intensity (EIT), and environmental impact per energy (EI_GJ), while FP was measured using ROE and NPM, (FS) measured by log of total assets. Panel regression technique was employed, including Random Effects and Fixed Effects models, with interaction terms to capture moderation effects. Model selection was ensured through diagnostic tests such as the Hausman test, variance inflation factor, Wooldridge test for serial correlation, heteroskedasticity, and cross-sectional dependence tests. The findings reveal that EIT exerts a positive and significant effect on ROE, meaning that efficient energy management enhances shareholder returns significantly. In contrast, EI_GJ shows a negative and significant relationship with return on equity, indicating that higher environmental burdens reduce profitability. For NPM, ECC exhibit a positive and significant direct effect in the non-moderated model, while EPC becomes positive and significant when firm size is introduced. Interaction effects involving firm size are insignificant across the two models. The study concludes that EA significantly influence financial performance, although firm size does not significantly moderate this relationship. It recommends that manufacturing firms strategically integrate efficiency-oriented and preventive environmental investments into their core operations to enhance profitability and long-term value creation.